Identification of TRAPPC9 and BAIAP2 Gene Polymorphisms and Their Association With Fat Deposition-Related Traits in Hu Sheep - Cui, Panpan; Wang, Weimin; Zhang, Deyin; Li, Chong; Huang, Yongliang; Ma, Zongwu; Wang, Xiaojuan; Zhao, Liming; Zhang, Yukun; Yang, Xiaobin; Xu, Dan; Cheng, Jiangbo; et al. (Frontiers in Veterinary Science, 2022)
Fat deposition is an important economic trait that are closely related to feed efficiency and carcass performance in livestock. In the present study, the fat deposition related traits of 1293 Hu lambs were measured and performed the descriptive statistical analysis, the result indicating the coefficient of variation all traits were great than 24%. In addition, the PCR amplification, Sanger sequencing, Kaspar genotyping and quantitative real-time PCR (qRT-PCR) were conducted to detected the single nucleotide polymorphisms (SNPs) of TRAPPC9 and BAIAP2 genes and expression features, and analyzed their association with fat deposition related traits in Hu sheep. Two novel mutations, TRAPPC9 g.57654 A > G and BAIAP2 g.46061 C > T, were identified in Hu sheep. The result of association analysis showed that the TRAPPC9 g.57654 A > G and BAIAP2 g.46061 C > T were both significantly association with the weight of tail fat, tail fat relative weight (body weight) and tail fat relative weight (carcass) (P < 0.05). Comprehensive effect analysis showed that there were significant differences between combined genotypes and tail fat and perirenal fat deposition. Simultaneously, the qRT-PCR results showed that the expression of TRAPPC9 and BAIAP2 genes were widely expressed, and the expression level of TRAPPC9 and BAIAP2 were higher in the small-tail group compared with in that of big-tail group (P < 0.01). These results provided important candidate molecular markers for reducing tail fat deposition in Hu sheep.